The dynamics of bioethical discussion in religious and philosophical doctrines about the living - Олександр Горбань; Руслана Мартич (Cхід, 2022)
The article presents a study of the formation and development of bioethical discourse based on the analysis of leading philosophical concepts, doctrines, and religious beliefs about the value of life in various manifestations of its being. The authors note that the beginning of axiological reflection on the problem of the living can be found in the works of ancient philosophers and the early Christian discourse as attempts to sacralise life. Moreover, the authors attribute a significant role in the development of bioethical discourse to the ethical doctrine of Kant and his opponents, representatives of the phenomenological direction of philosophical anthropology. Finally, the article notes that in modern conditions, bioethical discourse is concentrated around the axiological paradigm in the doctrine of the living. The various viewpoints are proposed to be grouped into two main approaches: the ethics of sacredness (sanctity) of life and the ethics of quality of life. These approaches have significant scientific potential, which allows for the development of bioethical doctrine, employing forming moral norms and imperatives of human behaviour, as well as establishing restrictions on human influence on the means and forms of existence of the living.